New record for Eriochrysis (Poaceae: Andropogoneae) in the State of Rio Grande do Sul, Brazil, and a key to the species of Eriochrysis in Brazil - Welker, Cassiano Aimberê Dorneles; Longhi-Wagner, Hilda Maria; de Souza-Chies, Tatiana Teixeira (Phytotaxa, 2012)
The genus Eriochrysis Beauvois (1812: 8) (Poaceae: Andropogoneae) includes ca. seven species from America, Africa, and India (Clayton & Renvoize 1986). It is characterized mainly by inflorescences with golden-brown to light-brown trichomes, and heterogamous spikelets: sessile spikelets with a bisexual flower and pedicelled spikelets with a pistillate flower. Six species of the genus occur in Brazil (Filgueiras & Welker 2012), of which three were previously reported for the State of Rio Grande do Sul: E. cayennensis Beauvois (1812: 8), E. holcoides (Nees 1829: 324) Kuhlmann (1922: 89) and E. villosa Swallen (1966: 90) (Welker & Longhi-Wagner 2012).